Recalibration of Authority in Handling Corruption Crimes after Law Number 20 of 2025: A KPK-Centered Investigation and Prosecution Model - Temmy Hastian; Klara Dawi (SIGn Jurnal Hukum, 2026)
The handling of corruption crimes following Law Number 20 of 2025 presents a problem of authority configuration because the Police, the Public Prosecution Service, and the KPK each retain legal bases of authority under positive law. This institutional plurality supports corruption eradication, but it may also create overlapping jurisdictions, uneven coordination, and risks of institutional conflicts of interest. This study aims to analyse the configuration of authority in the handling of corruption crimes under Law Number 20 of 2025, examine the risks of institutional conflicts of interest, and formulate a normative legal protection model based on recalibrating authority. This study applies normative-doctrinal legal research using statute, conceptual, and analytical-prescriptive approaches through the examination of primary and secondary legal materials. The findings show that, de lege lata, corruption crimes are still handled by a plurality of authorities, including the Police, the Public Prosecution Service, and the KPK. However, this plurality has not yet been supported by an operational design capable of determining the functional controller in a clear, objective, and accountable manner. This study formulates a de lege ferenda model of functional centralisation of the investigation and prosecution of corruption crimes within the KPK, while still allowing the involvement of Police personnel and Attorneys through an assignment mechanism within the Commission’s structure. This model requires amendments to sectoral Laws, strengthening of the KPK’s institutional capacity, coordination standards, ethical oversight, and institutional evaluation to reinforce legal certainty, independence, accountability, and the effectiveness of corruption eradication.